2022
DOI: 10.1039/d2em00045h
|View full text |Cite
|
Sign up to set email alerts
|

A review of simulation experiment techniques used to analyze wildfire effects on water quality and supply

Abstract: This review addresses the critical knowledge gap of techniques simulating combustion and heating characteristics present in natural wildfires and their use in assessing postfire impacts on water quality and quantity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…When trying to simulate natural fires, soil samples are often heated in laboratory muffle furnaces. However, using a muffle furnace can result in significant differences from natural fires since the samples are heated from all sides instead of just the soil surface (Brucker et al, 2022). A muffle furnace experiment conducted by Martínez et al (2022) confirmed that the hydraulic conductivity (both saturated and unsaturated) of sandy loam soil increased with temperature while the organic matter content of the soil decreased.…”
Section: Introductionmentioning
confidence: 98%
“…When trying to simulate natural fires, soil samples are often heated in laboratory muffle furnaces. However, using a muffle furnace can result in significant differences from natural fires since the samples are heated from all sides instead of just the soil surface (Brucker et al, 2022). A muffle furnace experiment conducted by Martínez et al (2022) confirmed that the hydraulic conductivity (both saturated and unsaturated) of sandy loam soil increased with temperature while the organic matter content of the soil decreased.…”
Section: Introductionmentioning
confidence: 98%
“…Wildfires are widespread ecosystem disturbances that burn millions of hectares each year and are beneficial within fire-adapted environments. However, over the past five decades, wildfires have become more frequent, severe (i.e., more vegetation and organic matter are consumed during burning), intense (i.e., higher temperatures and energy output), and are projected to increase in size. Thus, understanding how wildfires impact terrestrial ecosystems and the soils that support them is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory heating of soil samples in muffle furnaces is often used to simulate a natural fire. However, muffle furnaces heat the samples from all sides, making them significantly different from natural fires that only heat the soil surface [8]. Novák et al [9] found that water drop penetration time (WDPT) and saturated hydraulic conductivity of sandy soils from grassland increased with increasing the heating temperature from 20 to 250 • C. Stoof et al [10] revealed that heating soil to <200 • C did not change the properties of the studied sandy soil, but heating soil to >300 • C increased bulk density, clay and silt content, and decreased soil organic matter and sand content.…”
Section: Introductionmentioning
confidence: 99%